2001
DOI: 10.1046/j.1365-2141.2001.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of leucocyte adhesion directly observed in flowing whole blood in vitro

Abstract: Use of whole blood in adhesion assays allows analysis of the rheological and haematological factors that may influence adhesion, and avoids the need for isolation procedures that may modify the properties of leucocytes. We have adapted an in vitro flow model to allow videomicroscopy of leucocytes fluorescently labelled with rhodamine 6G (20 microg/ml) in anticoagulated whole blood. Blood was perfused at a range of wall shear rates (35-280/s) through a vertical glass capillary with a rectangular cross-section (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
42
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 37 publications
6
42
0
Order By: Relevance
“…Some elements of the study reproduce and support previous findings on the shear dependence of adhesion of leukocytes and platelets from flowing blood (3,41,50) and of the tendency for red cell aggregation to increase margination and adhesion of leukocytes (18,32,34). However, by newly analyzing the effects of varying shear rate and stress independently (by manipulating flow rate and suspending phase viscosity), we have been able to show that cell size critically affects the attachment process by influencing velocity and, especially, force experienced by cells at the vessel wall.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Some elements of the study reproduce and support previous findings on the shear dependence of adhesion of leukocytes and platelets from flowing blood (3,41,50) and of the tendency for red cell aggregation to increase margination and adhesion of leukocytes (18,32,34). However, by newly analyzing the effects of varying shear rate and stress independently (by manipulating flow rate and suspending phase viscosity), we have been able to show that cell size critically affects the attachment process by influencing velocity and, especially, force experienced by cells at the vessel wall.…”
Section: Discussionsupporting
confidence: 78%
“…Since cell velocity will limit time for formation of bonds and drag will increase the rate of dissociation of formed bonds (10), one can expect that attachment will be possible over a wider range of rates and stresses for platelets than leukocytes, without their needing to evolve even fasteracting receptors. In experimental studies of adhesion from flowing whole blood, leukocyte adhesion to selectins is restricted up to ϳ200 s Ϫ1 (3,27), while platelet adhesion to collagen operates at Ͼ1,000 s Ϫ1 (40,41). Nevertheless, the hypothesis that differences in leukocyte and platelet adhesive function arise from differences in size has not been tested under directly comparable conditions.…”
mentioning
confidence: 99%
“…A number of studies showed that WBC margination increases significantly as a function of decreasing shear rate (19,42,(45)(46)(47). Similar trends have been reported for particles.…”
Section: Shear Ratesupporting
confidence: 63%
“…Munn et al (23) showed that the addition of red blood cells to a lymphocyte suspension promoted adhesion of the lymphocytes to endothelial cells even at low hematocrit. Abbitt and Nash (1) showed that the adhesion of isolated neutrophils to P-selectin coatings was negligible when flowing through vertical tubes; however, when flowing in whole blood, many neutrophils were observed to adhere at equivalent volumetric flow rates. In a later work, Abbitt and Nash systematically …”
Section: Discussionmentioning
confidence: 99%